Keandalan Aplikasi Pengolah Kata Tak Berbayar Dalam Mendukung Kegiatan Pembelajaran Penulisan Karya Ilmiah - Andreas Tigor Oktaga; Siska Narulita; Martinus Apun Heses (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2022)
This article aims to review a free word processing application that can be used offline to support learning activities for writing scientific papers. Free application can be found in freeware and open-source. We collect data from freeware and open-source applications, for our selection based on the operating system that is widely used in Indonesia. Furthermore, selected applications that have a user interface design that is easy to understand for teachers and students. So users can quickly adapt. The evaluation results lead us to suggest that WPS Office as a reliable alternative. The drawback that has is the creation of a bibliography. However, it can still be overcome because the bibliography can still be done manually or by making a copy of the citation facility when using sources from Google Scholar.